Study the effect of government expenditure on GDP in Syria during the period (1990-2017) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aims to study the reality of government spending in Syria during the period (1990-2017) and its relationship with GDP growth, and to test the impact of current spending and investment spending on GDP at current prices during the period under study. The study found that government spending in both current and investment sectors had a positive and moral impact on GDP in prices. The results also showed that the impact of government spending on GDP on current prices during the period of the crisis was different from its effect during the pre-crisis period.